2021
DOI: 10.1039/d1cp00221j
|View full text |Cite
|
Sign up to set email alerts
|

Where do the counterions go? Tip-induced dissociation of self-assembled triazatriangulenium-based molecules on Au(111)

Abstract: Chemical coupling of functional molecules on top of so-called platform molecules allows the formation of functional self-assembled monolayers (SAMs). An often-used example of such a platform is triazatriangulenium (TATA), which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…57 The main objective is to simulate the experimental molecular gating by changing the charge state of the molecule in a self-consistent manner, and to deduce the corresponding electronic transmissions. 58–60 The molecular levels are shifted due to the gating and the resonance is obtained when a molecular level crosses the Fermi level. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…57 The main objective is to simulate the experimental molecular gating by changing the charge state of the molecule in a self-consistent manner, and to deduce the corresponding electronic transmissions. 58–60 The molecular levels are shifted due to the gating and the resonance is obtained when a molecular level crosses the Fermi level. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of counterions from an adsorbed monolayer has previously been observed for charged SAMs comprising triazatriangulenium (TATA)-based components, in independent studies using both XPS 7 and scanning tunnelling microscopy (STM). 53 It was suggested that counterion loss would imply a significant charge transfer to the substrate, 7 and that this may be favored by the electric field generated at an STM tip. 53 Computational studies further revealed that while a TATA + -BF4ion pair is stabilized by adsorption on a gold surface, its cohesive energy is reduced by addition of an electron to the system.…”
Section: Discussionmentioning
confidence: 99%
“…53 It was suggested that counterion loss would imply a significant charge transfer to the substrate, 7 and that this may be favored by the electric field generated at an STM tip. 53 Computational studies further revealed that while a TATA + -BF4ion pair is stabilized by adsorption on a gold surface, its cohesive energy is reduced by addition of an electron to the system. 53 It remains unclear whether counterion loss in TATA-based SAMs may occur prior to XPS or STM studies, and if so, what the mechanism of surface reduction might be.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither X-ray photoelectron spectroscopy (XPS) nor electrochemical STM in a HClO 4 electrolyte could detect BF 4 – moieties on the surface . Instead, the authors attribute this behavior to a strong interaction of the monolayer with the Au(111) substrate, leading to a screening of the positive charge of the cation and removal of the corresponding anion after adsorption of the monolayer. ,, Recently, we succeeded in clarifying the whereabouts of the BF 4 – anion on Au(111) by heat-aided deposition of TATA-BF 4 from 1,2,4-trichlorobenzene solvent . The counterions could be localized only under specific tunneling conditions.…”
Section: Introductionmentioning
confidence: 99%